High-wet-viscosity high-strength calcium phosphate-based bone repair material and preparation method thereof

By using oxidized sodium alginate and dopamine to form a cross-linked network structure with calcium phosphate, the method addresses adhesion and mechanical strength issues in bone repair materials, resulting in improved bonding and mechanical properties for bone repair applications.

CN119158085APending Publication Date: 2024-12-20SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411286938.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing calcium phosphate-based bone repair materials face challenges in achieving high adhesion to bone tissue in wet environments and insufficient mechanical strength, leading to issues such as agglomeration and reduced mechanical properties, which are exacerbated by poor compatibility and uneven dispersion with adhesive components.

Method used

A method involving the use of oxidized sodium alginate as an adhesive skeleton, combined with dopamine, to form a multiple network structure through cross-linking, enhanced by co-ball milling and mediated by gelatin, to create a high-wet viscosity and high-strength calcium phosphate-based bone repair material.

Benefits of technology

The method improves adhesion and mechanical strength by ensuring uniform dispersion and stability of calcium phosphate particles in the adhesive, forming a continuous network structure that enhances bonding and mechanical properties, suitable for bone repair applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158085A_ABST
    Figure CN119158085A_ABST
Patent Text Reader

Abstract

The invention discloses a high-wet-viscosity high-strength calcium phosphate-based bone repair material and a preparation method thereof, and belongs to the technical field of bone repair materials. The invention solves the problems of poor dispersibility and insufficient binding force with an adhesive of CPC which limits the wet viscosity and mechanical property improvement of the calcium phosphate bone cement (CPC). The preparation method comprises the following steps: preparing an oxidized sodium alginate-dopamine adhesive, uniformly grafting the oxidized sodium alginate-dopamine adhesive on the surface of CPC, and then adding a cross-linking agent to initiate cross-linking of the adhesive on the surface of an adhesive / CPC complex to form a multi-network structure, thereby obtaining the high-wet-viscosity and high-strength calcium phosphate-based bone repair material. An oxidized sodium alginate-dopamine adhesive is grafted on CPC to form an adhesive / CPC complex, then the oxidized sodium alginate-dopamine adhesive is crosslinked on the CPC to form a multi-network structure, and meanwhile, the wet viscosity and the mechanical strength of the adhesive / CPC complex are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bone repair materials, and in particular relates to a high-wet-viscosity and high-strength calcium phosphate-based bone repair material and a preparation method thereof. Background Art

[0002] In clinical bone tissue repair, when the bone defect exceeds the critical threshold (usually greater than 2 cm, depending on the anatomical site), even if the bone tissue has a certain regenerative capacity, bone implants are still needed to repair the bone defect. Although the "golden principle" of clinical orthopedics is autologous bone transplantation, there are risks such as limited donor sources and the need for secondary surgery, which increases the patient's pain; and the use of allogeneic or heterologous allogeneic bone has problems such as immunogenicity and infection, so artificial bone repair materials are still needed to reconstruct the normal structure and function of bone tissue. The ideal bone repair material needs to be able to temporarily replace the damaged bone tissue and ensure its supporting function, while also being able to promote the growth of new bone tissue. Bone repair materials need to maintain a firm bond with bone tissue and a stable structure in the presence of body fluids (blood) and repeated stress to maintain bone formation space. In addition, in some special occasions, such as alveolar bone regeneration, because the growth rate of fibrous tissue around the alveolar bone is higher than that of bone tissue, if the bone repair material cannot be tightly combined with the irregular alveolar bone and form a closed space, it will trigger an inflammatory response (fibrous wrapping). It can be seen that the special use environment requires that the bone repair material needs to be tightly integrated with the irregular damaged bone tissue under humid conditions and have sufficient mechanical strength itself.

[0003] Calcium phosphate-based materials have good biocompatibility, biodegradability, osteoconductivity and osteoinduction because they are similar to the inorganic components of bones. The slurry formed by mixing one or more calcium phosphate powders with a liquid phase is called "calcium phosphate cement" (CPC). CPC has good injectability and can fill irregular bone defects and solidify at the site of bone defects. CPC is composed of calcium phosphate salts such as hydroxyapatite. Its structure and composition are similar to human bones. After implantation in the body, it can fully contact with surrounding cells and tissues and form a good bone bond with natural bones. The Ca produced by its degradation 2+ and PO 4 3-It can participate in normal physiological processes and has been widely used as a tooth and bone repair material. However, CPC has almost no adhesion to bone tissue in a wet environment. It is currently only suitable for filling bone defects in other parts. It is difficult to meet the needs of large-size, bone-free (atrophy) bone repair, and it also leads to insufficient quality and quantity of new bone formed after use. On the other hand, the mechanical strength of CPC materials is insufficient, and the stability of the material structure in repeatedly stressed parts such as the spine and oral cavity cannot be guaranteed, which also limits the use of such materials in bone repair. At present, fixed pins are usually used to fix the formed scaffold to the bone defect to solve the CPC fixation problem; for the problem of insufficient compressive strength of CPC scaffolds, titanium mesh or polymer mesh (such as Peek, polytetrafluoroethylene) is usually used to wrap the scaffold to maintain the bone formation space; the scaffold wrapping mesh and fixed pins used need to be removed by secondary surgery, which also increases the risk of infection. Therefore, the problems that CPC bone repair materials still need to solve are: 1) giving CPC materials high adhesion to damaged bones in a wet environment so that they can be firmly combined with damaged bone tissue; 2) ensuring sufficient compressive strength of CPC materials.

[0004] The use of polymers with high viscosity in water combined with CPC can give it adhesion to the defective bone; the organic-inorganic composite material formed by adding polymers to CPC is also a common means to improve the strength of CPC. Based on the sticky protein secreted by the marine organism mussel through its foot disc, it can firmly adhere to the surface of various solids in salt and water environments. Studies have shown that the dopamine structural unit in the sticky protein is the source of its high viscosity. The bionic research on mussel sticky protein is an effective way to develop tissue adhesives that meet clinical needs. At present, a series of mussel bionic adhesives (abbreviated as adhesives) with high viscosity in wet environments have been obtained through methods such as direct functionalization of polymers with dopamine, self-polymerization or copolymerization of dopamine-modified monomers.

[0005] However, the adhesive / CPC bone repair material obtained by simply compounding CPC and adhesive currently faces the following problems:

[0006] 1) CPC has poor dispersibility in adhesives: To give CPC stickiness in water, the adhesive needs to be evenly wrapped on the surface of CPC particles. Currently, most adhesives are hydrophobic and have poor compatibility with hydrophilic CPC. During the compounding process with the adhesive, CPC particles usually tend to agglomerate and eventually settle, resulting in phase separation. It is difficult to obtain an adhesive / CPC composite with good dispersion, uniformity and stability, resulting in insufficient adhesion.

[0007] 2) Composite materials have insufficient mechanical strength: In organic-inorganic composite materials, the uniformity of the dispersion of inorganic components, the bonding force between inorganic and organic components, and the strength of the organic components themselves have a significant impact on their mechanical properties. Studies have shown that the better the dispersion of each component in an organic-inorganic composite material, the higher the material strength. If the inorganic components agglomerate, the agglomerated particles are only loosely bound by weak forces. When subjected to force, the agglomerates are easily destroyed, resulting in reduced mechanical properties of the composite material. Yasser Zare's research shows that the shear strength (τ) of the material is related to the degree of agglomeration of solid particles (A) as follows (Formula 1)

[0008]

[0009] Where: τ m , G, b B , λ are the shear stress of the polymer, the shear modulus of the inorganic component, the Burgers vector, and the distance between the nanoparticles; A is a parameter representing the degree of agglomeration of the inorganic particles, and the larger its value, the greater the degree of agglomeration. Like other CPCs with organic components, if the binder and the CPC therein are simply blended, CPC will tend to agglomerate in the binder due to the van der Waals force and the effect of the surface hydroxyl groups, making the internal structure of the binder / CPC composite material discontinuous, resulting in insufficient mechanical properties of the material.

[0010] The mechanical properties of the organic components in the composite material play an important role in the mechanical strength of the composite material. Adding organic components to inorganic CPC is easy to operate, mild in conditions, and conducive to improving biocompatibility, so it has become a common strategy to enhance the mechanical properties of CPC. However, due to the limitations of safety, usage conditions, and preparation processes, the molecular weight of the binder in the composite CPC is low and its own mechanical strength is insufficient, resulting in limited improvement or even decrease in the compressive strength of such composite CPC compared to pure CPC.

[0011] From the above analysis, it can be seen that the key to solving the problem of continuous and stable adhesion between adhesive / CPC composite bone repair materials and damaged bones and improving mechanical properties lies in how to evenly and accurately disperse CPC in the adhesive to form a homogeneous composite, while enhancing the bonding force between CPC and the adhesive and the strength of the adhesive itself. Summary of the invention

[0012] In view of the problem in the prior art of how to evenly and accurately disperse CPC in an adhesive to form a homogeneous composite and at the same time enhance the bonding force between CPC and the adhesive and the strength of the adhesive itself, the present invention provides a high wet viscosity and high strength calcium phosphate-based bone repair material and a preparation method thereof. The present invention firstly preferably uses hydrophilic oxidized sodium alginate as an adhesive skeleton to improve the compatibility of the adhesive with CPC; the adhesive is adsorbed and wrapped on the CPC surface through co-ball milling technology to generate a uniform and stable adhesive / CPC composite in situ; on this basis, the adhesive on the surface of the adhesive / CPC composite is initiated and controlled to undergo a cross-linking reaction to form a multiple network structure, thereby significantly improving the wet adhesion and mechanical properties of the CPC material.

[0013] The technical solution adopted by the present invention is as follows:

[0014] A method for preparing a high-wet viscosity and high-strength calcium phosphate-based bone repair material comprises the following steps:

[0015] S1: Preparation of oxidized sodium alginate-dopamine adhesive;

[0016] S2: uniformly grafting the oxidized sodium alginate-dopamine adhesive onto the CPC surface to form an adhesive / CPC complex;

[0017] S3: Add a cross-linking agent to the adhesive / CPC complex to induce cross-linking of the adhesive on its surface to form a multiple network structure, thereby obtaining a high-wet-viscosity and high-strength calcium phosphate-based bone repair material.

[0018] After adopting this technical solution, sodium alginate is first oxidized to oxidized sodium alginate, and then dopamine is grafted onto the oxidized sodium alginate. Since the oxidized sodium alginate has more active sites, the grafting rate of dopamine can be effectively improved to obtain a mussel biomimetic adhesive with high wet viscosity. After the oxidized sodium alginate-dopamine adhesive is precisely grafted onto CPC to form an adhesive / CPC complex, the stability and dispersibility of CPC in the adhesive can be effectively improved, and then the oxidized sodium alginate-dopamine adhesive on the surface of the adhesive / CPC complex is cross-linked to form a multiple network structure, while improving the wet adhesion and mechanical strength of the adhesive / CPC complex, and finally obtaining a high wet viscosity and high strength calcium phosphate-based bone repair material.

[0019] Preferably, in S2, the oxidized sodium alginate-dopamine adhesive is grown in situ on the CPC surface by co-ball milling, and the adhesive is precisely grafted onto CPC to form a uniform and stable adhesive / CPC complex.

[0020] After adopting this technical scheme, in order to solve the problems that the oxidized sodium alginate-dopamine adhesive has poor compatibility with CPC and CPC is easy to agglomerate, the present invention uses co-ball milling technology to make the oxidized sodium alginate-dopamine adhesive grow in situ on the CPC surface, and uses coordination bonds, hydrogen bonds, electrostatic adsorption and other effects to accurately graft the adhesive onto the surface of CPC particles, so that the Zeta potential of CPC particles is improved and the compatibility is enhanced, thereby obtaining an oxidized sodium alginate-dopamine adhesive / CPC complex with good dispersibility and strong stability.

[0021] Preferably, the ball milling medium used is zirconium oxide grinding balls, the ball milling time is 4-10 hours, and the rotation speed of the ball mill is 180-300 r / min.

[0022] Preferably, the mass ratio of oxidized sodium alginate-dopamine adhesive to CPC in S2 is 0.1-1:4.

[0023] After adopting this technical solution, the bonding force and mechanical strength of the adhesive / CPC complex can be optimized by adjusting the ratio of adhesive to CPC, thereby obtaining an adhesive / CPC composite bone repair material with high bonding force and high strength.

[0024] Preferably, gelatin is added to S3 to mediate cross-linking of the adhesive on the adhesive / CPC complex to form a connecting network structure.

[0025] After adopting this technical solution, in order to solve the problem of insufficient mechanical properties of the adhesive / CPC composite material, the present invention uses gelatin to mediate a cross-linking reaction of the adhesive, so that the adhesive on the CPC surface forms a network structure to obtain an oxidized sodium alginate-dopamine adhesive / CPC / gelatin composite bone repair material.

[0026] Preferably, the mass ratio of gelatin to the binder / CPC complex is 0.5-1:1.

[0027] After adopting this technical solution, the main body of the material is still CPC, which has sufficient strength while maintaining excellent osteogenic properties. The uniform addition of an appropriate proportion of adhesive can provide sufficient wet viscosity for bone cement while forming a dissipative structure in the adhesive / CPC complex through gelatin-mediated multiple cross-linking reactions, thereby improving its mechanical properties.

[0028] Preferably, the preparation method of the oxidized sodium alginate-dopamine adhesive in S1 comprises the following steps:

[0029] S11: oxidizing sodium alginate to obtain oxidized sodium alginate;

[0030] S12: reacting the obtained oxidized sodium alginate with dopamine hydrochloride in the absence of light under the action of an initiator to obtain an oxidized sodium alginate-dopamine adhesive.

[0031] After adopting this technical solution, the present invention first oxidizes sodium alginate with sodium periodate to provide more reactive sites for dopamine grafting, thereby improving the grafting rate; and by optimizing the grafting rate, an oxidized sodium alginate-dopamine adhesive with the strongest adhesion in water is obtained.

[0032] Preferably, sodium alginate is oxidized by sodium periodate in S11, and the mass ratio of sodium alginate to sodium periodate is 1:0.5-1.5.

[0033] After adopting this technical solution, the grafting rate is high when the mass ratio of sodium alginate to sodium periodate is 1:0.5-1.5, and the obtained high-wet viscosity and high-strength calcium phosphate-based bone repair material has higher viscosity. Compared with oxidants such as hydrogen peroxide and potassium permanganate, the oxidation degree of sodium alginate oxidized with sodium periodate is controllable, the reaction is rapid, and the oxidation process has less damage to its skeleton. It can maintain the integrity of the sodium alginate skeleton to the greatest extent while oxidizing rapidly.

[0034] Preferably, the mass ratio of dopamine hydrochloride to oxidized sodium alginate in S12 is 1:1-2.

[0035] After adopting this technical solution, the appropriate ratio of sodium periodate allows sodium alginate to be moderately oxidized, providing more active sites for dopamine grafting, while ensuring that the sodium alginate skeleton does not break due to oxidation and reduce the mechanical properties of the adhesive; the appropriate ratio of dopamine to oxidized sodium alginate allows dopamine to be evenly connected, and the sticky groups do not shield each other, thereby giving full play to the stickiness. The aldehyde group formed after the oxidation of sodium alginate can react with the amino group on gelatin through Schiff base to quickly cross-link the adhesive. Since the reaction is initiated by the oxidized sodium alginate aldehyde group, dopamine grafting does not affect the cross-linking between the two. In addition, compared with other cross-linking agents, gelatin has good biocompatibility and contains a variety of bioactive factors, which is beneficial to promote bone growth.

[0036] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0037] 1. The present invention uses hydrophilic sodium alginate as a skeleton to graft dopamine structural units to synthesize mussel biomimetic adhesives. Since sodium alginate has fewer active sites, directly grafting dopamine structural units has a low grafting rate and insufficient adhesive viscosity. Therefore, the present invention first oxidizes sodium alginate with sodium periodate to provide more reactive active sites for dopamine grafting, thereby increasing the grafting rate; and by optimizing the grafting rate, an oxidized sodium alginate-dopamine adhesive with the strongest adhesion in water is obtained.

[0038] 2. The present invention mainly adopts a method of in-situ generation of adhesive on the CPC surface, which mainly solves the problems of poor compatibility between CPC and adhesive, uneven distribution of direct composite adhesive, discontinuous internal structure of CPC / adhesive composite materials, and insufficient mechanical properties of the materials.

[0039] 3. In order to solve the problems that oxidized sodium alginate-dopamine adhesive has poor compatibility with CPC and CPC is easy to agglomerate, the present invention uses co-ball milling technology to wrap the adhesive on the surface of CPC particles by utilizing coordination bonds, hydrogen bonds, electrostatic adsorption and the like, thereby increasing the Zeta potential of CPC particles and enhancing the compatibility, thereby obtaining an oxidized sodium alginate-dopamine adhesive / CPC complex with good dispersibility and strong stability.

[0040] 4. In order to solve the problem of insufficient mechanical properties of adhesive / CPC composite materials, the present invention uses gelatin to mediate a cross-linking reaction of the adhesive, so that the adhesive on the surface of CPC forms a network structure to obtain an oxidized sodium alginate-dopamine adhesive / CPC / gelatin composite bone repair material; by adjusting the ratio of adhesive to CPC, the degree of adhesive cross-linking reaction can optimize the adhesion and mechanical strength of the adhesive / CPC complex, thereby obtaining a high-adhesion, high-strength adhesive / CPC composite bone repair material.

[0041] 5. The repair material of the present invention has good injectability in the initial stage and can be injected to fill the alveolar bone defect. The oxidized sodium alginate-dopamine adhesive has high viscosity in water, can be filled and firmly adhered to the bone defect and quickly solidified, and is mainly used for filling and repairing bone defects and vertebroplasty surgery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is the technical roadmap of the present invention;

[0043] Figure 2 This is the hydrogen spectrum of the oxidized sodium alginate-dopamine adhesive of the present invention. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0045] Example 1

[0046] like Figure 1 As shown, a method for preparing a high-wet viscosity and high-strength calcium phosphate-based bone repair material comprises the following steps:

[0047] S1: Preparation of oxidized sodium alginate-dopamine adhesive;

[0048] S11: Dissolve 1 part of sodium alginate and 1 part of sodium periodate in deionized water, react in the dark for 24 hours, then dialyze the solution in deionized water for three days (dialysis bag molecular weight cutoff: 7000Da), change the water every 8-12 hours, freeze-dry the dialyzed solution at -20°C to obtain the product oxidized sodium alginate; the oxidized sodium alginate obtained by reacting sodium alginate and sodium periodate in a mass ratio of 1:1 has the most active sites and is most conducive to dopamine grafting, and the dopamine grafting rate can reach 30%.

[0049] S12: Dissolve 1.3 parts of the obtained oxidized sodium alginate and 1 part of dopamine hydrochloride in deionized water, use N-hydroxysuccinimide as an initiator, and react in the dark for 24 hours at a pH of 8 and a temperature of 60° C. to obtain an oxidized sodium alginate-dopamine adhesive. The hydrogen spectrum of the obtained oxidized sodium alginate-dopamine adhesive is as follows: Figure 2 As shown; under this ratio condition, compared with the bionic adhesive prepared by other ratios, its structure is more stable and the content of structural units with adhesion in water is more reasonable (storage modulus G'=3000Pa and loss modulus G"=120Pa).

[0050] S2: Add 1 part of sodium alginate-dopamine binder, 4 parts of CPC and 250 zirconium oxide grinding balls (Φ=10 mm) into a ball mill, and mill them in the ball mill for 6 hours (ball mill speed 250 r / min) to obtain a solid phase powder of the binder / CPC complex.

[0051] S3: dissolving gelatin in 0.1 mol / L phosphate buffer to prepare a gelatin solution with a concentration of 20 w / v%;

[0052] One part of the solid phase powder of the adhesive / CPC complex obtained from S2 and one part of a gelatin solution with a concentration of 20 w / v% are mixed to obtain a mixed slurry; the obtained mixture is incubated at 60°C for 0.5 hour to induce a cross-linking reaction between the oxidized sodium alginate-dopamine adhesive and the gelatin, so that the oxidized sodium alginate-dopamine adhesive forms a network structure, thereby obtaining a high-wet viscosity and high-strength calcium phosphate-based bone repair material.

[0053] Example 2

[0054] A method for preparing a high-wet viscosity and high-strength calcium phosphate-based bone repair material comprises the following steps:

[0055] S1: Preparation of oxidized sodium alginate-dopamine adhesive;

[0056] S11: Dissolve 1 part of sodium alginate and 0.5 part of sodium periodate in deionized water, and react for 24 hours in a dark environment. Then, dialyze the solution in deionized water for three days (dialysis bag molecular weight cutoff: 7000Da), and change the water every 8-12 hours. The dialyzed solution is freeze-dried at -20°C to obtain the product, oxidized sodium alginate.

[0057] S12: dissolving 1.5 parts of the obtained oxidized sodium alginate and 1 part of dopamine hydrochloride in deionized water, using N-hydroxysuccinimide as an initiator, reacting in the dark at a pH of 8 and a temperature of 60° C. for 24 hours to obtain an oxidized sodium alginate-dopamine adhesive;

[0058] S2: 0.5 parts of sodium alginate-dopamine binder, 4 parts of CPC and 250 zirconium oxide grinding balls (Φ=10 mm) were added to a ball mill, and the mixture was milled for 6 h (ball mill speed 250 r / min) to obtain a solid phase powder of the binder / CPC composite;

[0059] S3: dissolving gelatin in 0.1 mol / L phosphate buffer to prepare a gelatin solution with a concentration of 20 w / v%;

[0060] 1 part of the solid phase powder of the adhesive / CPC complex obtained from S2 and 0.8 part of a gelatin solution with a concentration of 20 w / v% are mixed to obtain a mixed slurry; the obtained mixture is incubated at 60°C for 0.5 hour to induce a cross-linking reaction between the oxidized sodium alginate-dopamine adhesive and the gelatin, so that the oxidized sodium alginate-dopamine adhesive forms a network structure, thereby obtaining a high-wet viscosity and high-strength calcium phosphate-based bone repair material.

[0061] Example 3

[0062] A method for preparing a high-wet viscosity and high-strength calcium phosphate-based bone repair material comprises the following steps:

[0063] S1: Preparation of oxidized sodium alginate-dopamine adhesive;

[0064] S11: Dissolve 1 part of sodium alginate and 1 part of sodium periodate in deionized water, and react for 24 hours in a dark environment. Then, dialyze the solution in deionized water for three days (dialysis bag molecular weight cutoff: 7000Da), and change the water every 8-12 hours. The dialyzed solution is freeze-dried at -20°C to obtain the product, oxidized sodium alginate.

[0065] S12: dissolving 1.3 parts of the obtained oxidized sodium alginate and 1 part of dopamine hydrochloride in deionized water, using N-hydroxysuccinimide as an initiator, reacting in the dark at a pH of 8 and a temperature of 60° C. for 24 hours to obtain an oxidized sodium alginate-dopamine adhesive;

[0066] S2: 0.5 parts of sodium alginate-dopamine binder, 4 parts of CPC and 250 zirconium oxide grinding balls (Φ=10 mm) were added to a ball mill, and the mixture was milled for 6 h (ball mill speed 250 r / min) to obtain a solid phase powder of the binder / CPC composite;

[0067] S3: dissolving gelatin in 0.1 mol / L phosphate buffer to prepare a gelatin solution with a concentration of 20 w / v%;

[0068] One part of the solid phase powder of the adhesive / CPC complex obtained from S2 and 0.6 parts of a gelatin solution with a concentration of 20 w / v% are mixed to obtain a mixed slurry; the obtained mixture is incubated at 60°C for 0.5 hours to induce a cross-linking reaction between the oxidized sodium alginate-dopamine adhesive and the gelatin, so that the oxidized sodium alginate-dopamine adhesive forms a network structure, thereby obtaining a high-wet viscosity and high-strength calcium phosphate-based bone repair material.

[0069] Example 4

[0070] A method for preparing a high-wet viscosity and high-strength calcium phosphate-based bone repair material comprises the following steps:

[0071] S1: Preparation of oxidized sodium alginate-dopamine adhesive;

[0072] S11: Dissolve 1 part of sodium alginate and 1 part of sodium periodate in deionized water, and react for 24 hours in a dark environment. Then, dialyze the solution in deionized water for three days (dialysis bag molecular weight cutoff: 7000Da), and change the water every 8-12 hours. The dialyzed solution is freeze-dried at -20°C to obtain the product, oxidized sodium alginate.

[0073] S12: dissolving 1.3 parts of the obtained oxidized sodium alginate and 1 part of dopamine hydrochloride in deionized water, using N-hydroxysuccinimide as an initiator, reacting in the dark at a pH of 8 and a temperature of 60° C. for 24 hours to obtain an oxidized sodium alginate-dopamine adhesive;

[0074] S2: Add 0.3 parts of sodium alginate-dopamine binder, 4 parts of CPC and 250 zirconium oxide grinding balls (Φ=10 mm) into a ball mill, and mill them in the ball mill for 6 hours (ball mill speed 250 r / min) to obtain a solid phase powder of the binder / CPC complex.

[0075] S3: dissolving gelatin in 0.1 mol / L phosphate buffer to prepare a gelatin solution with a concentration of 20 w / v%;

[0076] 1 part of the solid phase powder of the adhesive / CPC complex obtained from S2 and 0.8 part of a gelatin solution with a concentration of 20 w / v% are mixed to obtain a mixed slurry; the obtained mixture is incubated at 60°C for 0.5 hour to induce a cross-linking reaction between the oxidized sodium alginate-dopamine adhesive and the gelatin, so that the oxidized sodium alginate-dopamine adhesive forms a network structure, thereby obtaining a high-wet viscosity and high-strength calcium phosphate-based bone repair material.

[0077] Comparative Example 1

[0078] This comparative example is basically the same as Example 1, except that: 1 part of sodium alginate and 1 part of dopamine hydrochloride are dissolved in deionized water, N-hydroxysuccinimide is used as an initiator, and the reaction is carried out in the dark at a pH of 8 and a temperature of 60° C. for 24 hours to obtain a sodium alginate-dopamine adhesive, and the sodium alginate-dopamine adhesive is used to replace the oxidized sodium alginate-dopamine adhesive in Example 1.

[0079] Comparative Example 2

[0080] This comparative example is basically the same as Example 1, except that: in S2, ball milling is not performed, and the oxidized sodium alginate-dopamine binder and 4 parts of CPC are directly mixed uniformly by stirring;

[0081] Comparative Example 3

[0082] This comparative example is basically the same as Example 1, except that S3 is not performed, and the solid phase powder of the adhesive / CPC complex is directly used as the calcium phosphate-based bone repair material.

[0083] Comparative Example 4

[0084] This comparative example is basically the same as Example 1, except that: in S11, 1 part of sodium alginate and 0.1 part of sodium periodate are dissolved in deionized water and reacted for 24 hours in the dark.

[0085] Comparative Example 5

[0086] This comparative example is basically the same as Example 1, except that: in S11, 1 part of sodium alginate and 2 parts of sodium periodate are dissolved in deionized water and reacted in the dark for 24 hours.

[0087] Comparative Example 6

[0088] This comparative example is substantially the same as Example 1, except that 0.5 parts of the obtained oxidized sodium alginate and 1 part of dopamine hydrochloride are dissolved in deionized water.

[0089] Comparative Example 7

[0090] This comparative example is substantially the same as Example 1, except that 3 parts of the obtained oxidized sodium alginate and 1 part of dopamine hydrochloride are dissolved in deionized water.

[0091] Comparative Example 8

[0092] This comparative example is basically the same as Example 1, except that: in S2, 3 parts of oxidized sodium alginate-dopamine binder, 4 parts of CPC and 250 zirconium oxide grinding balls (Φ=10 mm) are added to a ball mill and ball milled in the ball mill for 6 hours.

[0093] Comparative Example 9

[0094] This comparative example is basically the same as Example 1, except that: 1 part of the solid phase powder of the binder / CPC composite obtained from S2 and 0.1 part of a gelatin solution with a concentration of 20 w / v% are mixed to obtain a mixed slurry.

[0095] Comparative Example 10

[0096] This comparative example is basically the same as Example 1, except that: 1 part of the solid phase powder of the binder / CPC composite obtained from S2 and 2 parts of a gelatin solution with a concentration of 20 w / v% are mixed to obtain a mixed slurry.

[0097] Comparative Example 11

[0098] This comparative example is substantially the same as Example 1, except that tannic acid is used instead of gelatin.

[0099] Comparative Example 12

[0100] This comparative example is basically the same as Example 1, except that sodium alginate is oxidized with hydrogen peroxide.

[0101] The performance test data of Examples 1-4 and Comparative Examples 1-10 are shown in Table 1. In order to highlight the differences, the same parts as Example 1 are not filled in: Generally, the Zeta potential of solid particles reflects their charge. The greater the charge carried by the particles, the greater the repulsion between the particles, and the smaller the tendency of agglomeration. Therefore, the Zeta potential (eV) is usually used to evaluate its dispersibility. The larger the absolute value of the Zeta potential, the better the dispersion performance.

[0102] Table 1

[0103]

[0104]

[0105] It can be seen from the above examples and comparative examples that Example 1 has the best effect, because the oxidized sodium alginate obtained by reacting sodium alginate and sodium periodate in a mass ratio of 1:1 has the most active sites and is most conducive to dopamine grafting, and the dopamine grafting rate can reach 30%. Compared with the biomimetic adhesives prepared by using dopamine and oxidized sodium alginate in a molar ratio of 1:1.3, at pH 8 and temperature 60°C, the oxidized sodium alginate-dopamine adhesive has a more stable structure and a more reasonable content of structural units with adhesion in water (storage modulus G'=3000Pa and loss modulus G"=120Pa), and in Example 1, the oxidized sodium alginate-dopamine adhesive is co-milled in a ratio of 1:4. During this process, the oxidized sodium alginate-dopamine adhesive is wrapped on the surface of CPC particles through coordination bonds, hydrogen bonds, electrostatic adsorption, etc., so that the absolute value of its Zeta potential is increased, and the repulsion between CPC particles is increased. The obtained oxidized sodium alginate-dopamine adhesive / CPC has good dispersibility and high uniformity.

[0106] Under the mediation of gelatin, the oxidized sodium alginate-dopamine adhesive undergoes a cross-linking reaction, the molecular weight of the organic component increases, and the strength is improved, so the mechanical properties of the composite are enhanced. The bovine bone specimens connected by the above-mentioned oxidized sodium alginate-dopamine adhesive / CPC / gelatin bone repair material were subjected to a lap shear test, and the bonding ability of the adhesive was evaluated by comparing it with the data of pure CPC measured by the same method. In Example 1, the bonding strength of the specimen in water before the adhesive was cured was τ=186.0±21.2kPa, while pure CPC had no bonding force, which shows that the oxidized sodium alginate-dopamine adhesive / CPC / gelatin bone repair material has a strong bonding force on bone tissue. The compressive strength of the oxidized sodium alginate-dopamine adhesive / CPC in Example 1 before cross-linking was τ=543.68±72.34 kPa, and the compressive strength of the oxidized sodium alginate-dopamine adhesive / CPC / gelatin bone repair material in Example 1 after gelatin-mediated adhesive cross-linking was τ=787.64±67.11 kPa. The compressive strength of the bone repair material was improved after cross-linking.

[0107] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. A method for preparing a high-wet viscosity and high-strength calcium phosphate-based bone repair material, characterized in that: The following steps are involved: S1: Preparation of oxidized sodium alginate-dopamine adhesive; S2: Grafting oxidized sodium alginate-dopamine adhesive onto CPC to form an adhesive / CPC composite; S3: adding a cross-linking agent to the adhesive / CPC complex to cross-link the adhesive on its surface to form a multiple network structure, thereby obtaining a high-wet-viscosity and high-strength calcium phosphate-based bone repair material.

2. The method for preparing the high-wet viscosity and high-strength calcium phosphate-based bone repair material according to claim 1, characterized in that: In S2, the oxidized sodium alginate-dopamine adhesive is grown in situ on the CPC surface by co-ball milling, and the oxidized sodium alginate-dopamine adhesive is grafted onto the CPC surface to form a uniform and stable adhesive / CPC complex.

3. The method for preparing the high-wet-viscosity high-strength calcium phosphate-based bone repair material according to claim 2, characterized in that: The ball milling medium used in the co-ball milling is zirconia grinding balls, the ball milling time is 4-10 hours, and the speed of the ball mill is 180-300r / min.

4. The method for preparing the high-wet viscosity and high-strength calcium phosphate-based bone repair material according to claim 1, characterized in that: The mass ratio of oxidized sodium alginate-dopamine adhesive to CPC in S2 is 0.1-1:

4.

5. The method for preparing the high-wet-viscosity high-strength calcium phosphate-based bone repair material according to claim 1, characterized in that: The addition of gelatin into S3 mediates the cross-linking of the adhesive on the adhesive / CPC complex to form a connecting network structure.

6. The method for preparing the high-wet-viscosity high-strength calcium phosphate-based bone repair material according to claim 5, characterized in that: The mass ratio of gelatin to binder / CPC complex is 0.5-1:

1.

7. The method for preparing the high-wet viscosity and high-strength calcium phosphate-based bone repair material according to any one of claims 1 to 6, characterized in that: The preparation method of the oxidized sodium alginate-dopamine adhesive in S1 comprises the following steps: S11: oxidizing sodium alginate to obtain oxidized sodium alginate; S12: reacting the obtained oxidized sodium alginate with dopamine hydrochloride in the absence of light under the action of an initiator to obtain an oxidized sodium alginate-dopamine adhesive.

8. The method for preparing the high-wet viscosity and high-strength calcium phosphate-based bone repair material according to claim 7, characterized in that: In S11, sodium periodate is used to oxidize sodium alginate, and the mass ratio of sodium alginate to sodium periodate is 1:0.5-1.

5.

9. The method for preparing the high-wet-viscosity high-strength calcium phosphate-based bone repair material according to claim 7, characterized in that: The mass ratio of dopamine hydrochloride to oxidized sodium alginate in S12 is 1:1-2.

10. A high-wet-viscosity and high-strength calcium phosphate-based bone repair material obtained by the preparation method according to claims 1-9.